2022
DOI: 10.1093/conphys/coac059
|View full text |Cite
|
Sign up to set email alerts
|

Selecting auditory alerting stimuli for eagles on the basis of auditory evoked potentials

Abstract: Development of wind energy facilities results in interactions between wildlife and wind turbines. Raptors, including bald and golden eagles, are among the species known to incur mortality from these interactions. Several alerting technologies have been proposed to mitigate this mortality by increasing eagle avoidance of wind energy facilities. However, there has been little attempt to match signals used as alerting stimuli with the sensory capabilities of target species like eagles. One potential approach to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…There have been some attempts to investigate the effects of noise on the processing of more complex signals using the AEP method. For instance, Goller et al (2022) presented tones, amplitude modulated, and frequency modulated signals to bald eagles (Haliaeetus leucocephalus) and golden eagles (Aquila chrysaetos) in either white or pink noise. They found that noise had a substantial effect on less dynamic signals (i.e., those with less modulation) but that processing of more modulated signals was less effected by the addition of noise.…”
Section: Comparative Avian Auditory Processing In Noisementioning
confidence: 99%
“…There have been some attempts to investigate the effects of noise on the processing of more complex signals using the AEP method. For instance, Goller et al (2022) presented tones, amplitude modulated, and frequency modulated signals to bald eagles (Haliaeetus leucocephalus) and golden eagles (Aquila chrysaetos) in either white or pink noise. They found that noise had a substantial effect on less dynamic signals (i.e., those with less modulation) but that processing of more modulated signals was less effected by the addition of noise.…”
Section: Comparative Avian Auditory Processing In Noisementioning
confidence: 99%